Pergeseran Adat Perkawinan Masyarakat Meranjat, Ogan Ilir, Sumatra Selatan - Henny Rosa Putri; Aman Aman (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
This article discusses the marriage system that occurred in the Meranjat community, Ogan Ilir, South Sumatra. This article is based on problems that are developing in this time in the village of Meranjat that various traditions are being abandoned, including those traditions of marriage. This article aims to explain the movement of the procedures of wedding customs in Meranjat village and the various values of the traditionhich is being lost. This article was an ethnography research that would be described qualitatively. Data were obtained both through observation, literature study and interview with historian, official government, customary holder, and persons who perform Meranjat wedding customs. The results of this article indicate that there is a movement in the procedures for implementing marriage in Meranjat. This is due to the times that require more practicality. There are also other factors, such as the economical and development technology. As a result, the meaning of the traditions are also danger of being lost.